2011
DOI: 10.1080/02667363.2011.624309
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of consultation sessions for foster carers and adoptive parents

Abstract: The aim of the study was to examine whether consultation sessions provided by educational psychologists (EPs) offer a useful way of supporting foster and adoptive parents. Feedback was collected from 101 EPs and 78 foster and adoptive parents through the use of a short questionnaire at the end of each session. As might be expected, educational issues were the main focus of the sessions, although other areas such as behaviour management and emotional well-being were also addressed. In general, both EPs and care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Evaluations which collect multiple types of data from different sources are presented by Turner et al (2010) and Osborne and Alfano (2011). A tool such as the one developed by Turner et al (2010) could also provide an additional source of information to consolidate the evidence by recording practitioners' reflections, that is, their thinking, knowing, feeling and seeing.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluations which collect multiple types of data from different sources are presented by Turner et al (2010) and Osborne and Alfano (2011). A tool such as the one developed by Turner et al (2010) could also provide an additional source of information to consolidate the evidence by recording practitioners' reflections, that is, their thinking, knowing, feeling and seeing.…”
Section: Discussionmentioning
confidence: 99%
“…EPs contribute to mental health promotion in schools at various levels (Atkinson et al, 2014;Fallon, 2017). Whilst literature has examined EP practice in delivery of therapeutic interventions (Simpson & Atkinson, 2019) there is limited evidence in relation to EP routine mental health casework in schools, other than that relating to the use of generic consultation skills in supporting adults to manage challenging behaviour (Hayes & Stringer, 2016;Nolan & Moreland, 2014;Nugent et al, 2014;Osborne & Alfano, 2011). The need for further research is underpinned by the following: "The role of education in tackling children's mental health issues must go beyond the oft-quoted solution of greater provision of counselling to individual pupils" (AEP, 2017, p. 1) and "[EPs] can play a particular and valuable role in [.…”
Section: The Role Of Eps In Supporting Student Mental Health In Schoolsmentioning
confidence: 99%
“…A range of services that were nearby and delivered by professionals (Murray et al 2011), educational, health and social areas was identified. Schools (Benbenishty & Schiff 2009) of higher education (Mennen & Trickett 2011) with special education services (Bywater et al 2011) provided school professionals (Edwards 2009) with credentials (Hook & Courtney 2011) such as teachers (Hegar & Rosenthal 2011) and psychologists (Osborne & Alfano 2011) were needed. In addition, general health care (Dowdell et al 2009;Schneiderman & Villagrana 2010), care for serious medical issues (Geltman et al 2008) including mental health services (Galehouse et al 2010) as well as treatments, such as medication (Crismon & Argo 2009) were needed.…”
Section: Servicesmentioning
confidence: 99%
“…Schools (Benbenishty & Schiff ) of higher education (Mennen & Trickett ) with special education services (Bywater et al . ) provided school professionals (Edwards ) with credentials (Hook & Courtney ) such as teachers (Hegar & Rosenthal ) and psychologists (Osborne & Alfano ) were needed. In addition, general health care (Dowdell et al .…”
Section: Literature Reviewmentioning
confidence: 99%